2003
DOI: 10.1034/j.1399-6576.2003.00047.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of preoperative oral carbohydrates and peptides on postoperative endocrine response, mobilization, nutrition and muscle function in abdominal surgery

Abstract: Significant postoperative decrease in glycogen synthase activity in the muscle biopsies was reduced in the intervention groups, and in combination, the intervention groups had a less reduced quadriceps strength after one week (-10% vs. -16%, NS) and one month (-5% vs. -13%, P < 0.05). Minor changes in the endocrine response to surgery were found without differences between the groups, and there were no differences between the groups in ambulation time, nutritional intake or subjective measures of wellbeing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
108
4
12

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(138 citation statements)
references
References 20 publications
13
108
4
12
Order By: Relevance
“…Previous studies investigating preoperative carbohydrate loading showed that levels of FFA were similar between treated and control groups following surgery, as seen in our findings (16,81,82). The reasons behind this are unclear.…”
Section: Discussionsupporting
confidence: 54%
“…Previous studies investigating preoperative carbohydrate loading showed that levels of FFA were similar between treated and control groups following surgery, as seen in our findings (16,81,82). The reasons behind this are unclear.…”
Section: Discussionsupporting
confidence: 54%
“…142 Overnight treatment with glucose prevents postoperative decrease in insulin sensitivity 30,146 and early loss of protein after gastrointestinal surgery [147][148][149] and augments voluntary muscle function. 150 Clinical studies conducted in small patient populations reported better outcomes with preoperative nutrition 112,130,[151][152][153][154] and emphasize that avoidance of fasting makes patients less susceptible to complications and may decrease hospital length of stay. 27,[154][155][156] In contrast, the results of a larger randomized controlled trial showed no significant benefit.…”
Section: Assessment Of Catabolism Before Surgerymentioning
confidence: 99%
“…Both of these changes in glucose metabolism cause hyperglycemia. In addition, the postoperative patient has a defective glycogen synthase activity for up to 1 month postoperatively (Henriksen et al 2003), and this may in part explain the reduced muscle strength that can prevail for a long period of time after a major operation.…”
Section: Postoperative Insulin Resistancementioning
confidence: 99%
“…Secondly, insulin is one of the main anabolic hormones in the body and when resistance sets in, muscle protein losses increase (Crowe et al 1984, Yuill et al 2005. Thirdly, when glucose uptake and storage is reduced in muscle and proteins are lost, these two factors will reduce muscle strength (Henriksen et al 2003).…”
Section: Postoperative Insulin Resistancementioning
confidence: 99%